Aboveground litter production and bioelement potential return in an evergreen oak (Quercus rotundifolia) woodland near Salamanca (Spain) - Martin, A; Gallardo, J F; Santa Regina, I (Ann. For. Sci., 1996)
Total aboveground production of trees has been determined in a Quercus rotundifolia evergreen oak woodland developed over a chromic Luvisol. The woodland is located close to the city of Salamanca (central-western Spain). Litter fall occurs throughout the year, with a maximum from April to June owing to leaf fall. Mean litter production is 1.9 Mg ha-1 year-1, although variations from year to year are observed, mostly due to water stress in summer. The mean area of influence of litter fall of each tree is about 4 m outside the crown shadow and the leaf percentage (55%) over the total aboveground litter production shows that the system is mature. Tree inflorescences are found to have the highest concentration in bioelements, although the latter are mostly returned through the leaves (with the exception of K).
Keywords: biogeochemical cycles; evergreen oak; litter fall; potential return of bioelements; Quercus rotundifolia Lam

Dynamics of bioelements during leaf decomposition in three forest ecosystems of semiarid climate in the Duero Basin - Hernández, M I; Santa Regina, I; Gallardo, J F (Arid Soil Research and Rehabilitation, 1995)
The dynamics of bioelements lost during leaf litter decomposition were experimentally determined in three forest ecosystems located in a semiarid zone of the Duero Basin, Province of Zamora, Spain, during 2 years. The three ecosystems were a climax Quercus rotundifolia (evergreen oak) woodland, a paraclimax Pinus pinea (stone pine) forest, and a disclimax P. pinaster (maritime pine) forest. The total content of bioelements found in the litter was low in relation to other forest ecosystems: 27, 14, and 8 kg N ha?1 in Q. pyrenaica, P. pinea, and P. pinaster, respectively; 17, 10, and 9 kg Ca ha?1, respectively; about 2 kg P ha?1, 4 kg K ha?1, and 5 kg Mg ha?1 in the three forests. The Q. rotundifolia woodland potentially returns a greater amount of N and Ca than both Pinus forests. An in situ litter bag method was used for the determination of dynamics of the decomposing leaves. A progressive loss of C, P, and Mg in the decomposing oak leaves and pine needles, and a sharp loss of K were observed; by comparison, a tendency to maintain N and Ca was seen. Pinus pinaster forest had the lowest annual N and P return.
doi: 10.1080/15324989509385911
Keywords: biogeochemical cycles; litter decomposition; pine forests; Quercus rotundifolia; semiarid forests